THE APPLICATION OF DEMOCRATIC PRINCIPLES IN INDONESIA'S ELECTORAL SYSTEM: THE APPLICATION OF DEMOCRATIC PRINCIPLES IN INDONESIA'S ELECTORAL SYSTEM - Irawan, Taufik; Suganda, Atma; Rattanapun, Supot (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
This research examines the application of democratic principles in the General Election system in Indonesia, focusing on aspects of popular sovereignty, equal suffrage, freedom of choice, and transparency and accountability. Based on a normative juridical approach, this research finds that although the Indonesian electoral system has adopted the principle of LUBER JURDIL and is regulated by various regulations that support democracy, its implementation still faces serious challenges. The practices of money politics, identity politics, and the spread of hoaxes still threaten the quality of elections and damage their integrity. This research provides recommendations that election supervision be strengthened, political education be expanded, and law enforcement against election violations be sharpened to improve the quality of democracy in Indonesia.